Endogenous Development as Strategic Resource of Agrarian Growth in Conditions of Global Challenges - A. V. Golubev (Вестник Российского экономического университета имени Г. В. Плеханова)
Each stage of the development requires correction of economic course, especially in conditions of global challenges. The period of orientation to external sources of growth at the expense of selling raw materials and power products abroad is over, thus it is necessary to pass over to endogenous development of Russian economy, especially agriculture. Information provided in the article gives evidence to a big share of exported resources in respect to the volume of their production or extraction. Four fifth of mineral fertilizers produced in the country is sold abroad, though home agriculture uses them in insufficient volume. Additional amounts of mineral fertilizers in Russian fields could increase the volume of food that is in demand on global markets. Power resources that cannot be used due to anti-Russian sanctions could be directed to internal needs, which could give an opportunity to convert them into goods with high added value. Putting resources that were not used by western countries in home economy can create extra capacities and extend taxation base, which could compensate for losses on foreign market. In agriculture priority shall be given to the development of local economy mobilizing local labour and material resources, which apart from production effect could provide opportunities for resolving a number of social and economic problems caused by big agricultural producers. The author came to the conclusion about the promising nature of endogenous development, which can ensure the quality of Russian economy growth and its agrarian sector.